138. Focused Outpatient Antibiograms: Time for Widespread Implementation?. (31st December 2020) - Manandhar, Sabina; Cook, Paul P; Schwartz, Michael D; Duncan, Heather M
Abstract: Background: Significant antimicrobial use occurs in outpatient settings, making this an important area for expanding stewardship. Data show over 260 million annual prescriptions in the U.S. Family practitioners prescribed the most antibiotic courses (24%) 1 . Urinary Tract Infections (UTI) comprise one of the most common indications for antibiotics. In this study, antibiogram data were compiled for urinary isolates of E coli collected from all outpatients as well as Family Medicine-specific (FM) clinics in an academic medical center in Eastern NC. The objective is to identify susceptibility variations for E. coli from urine isolates specific to combined outpatient and academic FM clinics compared to composite non-intensive care unit (ICU) data. Also, assess impact of providers' knowledge/access to a focused antibiogram on choice of empiric therapy. Methods: Data were electronically obtained from the microbiology laboratory at Vidant Health (VH), a large regional system serving over 1.4 million people from 29 counties in Eastern NC. All urine cultures with E. coli from 9/2018 - 9/2019 were included. Two focused antibiograms were then developed via MedMind. A pre and post intervention survey was conducted with FM practitioners, including residents. Intervention was defined as a brief talk to educate providers about variations identified via focused antibiograms. Survey results were compared to assess for intent to change practice. Results: Pre-survey data are noted in Figure 1. Post-survey changes are described in Figure 2 noting that 100% of respondents now felt a need to have access to focused antibiogram data. There were 1107 E coli urinary isolates for all outpatients and 104 for FM clinics only. Figure 3 highlights key differences in antibiogram data, especially enhanced susceptibilities for common antibiotics in FM-specific clinics when compared to composite institutional data. Pre-Intervention Survey Post-Intervention Survey Comparison of Antibiogram Conclusion: Composite hospital antibiograms may not be optimal for determining empiric UTI treatment in the community and antibiotic selections thought to be suboptimal in an institution may be effective in outpatient settings. Thus, antibiograms developed specifically for outpatient clinics, especially in academic centers, have potential to greatly enhance appropriate care. Disclosures: Paul P. Cook, MD, Contrafect (Grant/Research Support, Scientific Research Study Investigator)Gilead (Grant/Research Support, Scientific Research Study Investigator)Leonard-Meron (Grant/Research Support, Scientific Research Study Investigator)Lilly (Grant/Research Support, Scientific Research Study Investigator)